2020
DOI: 10.1007/s10389-020-01330-y
|View full text |Cite
|
Sign up to set email alerts
|

Successful implementation of self-management health innovations

Abstract: Background Literature on self-management innovations has studied their characteristics and position in healthcare systems. However, less attention has been paid to factors that contribute to successful implementation. This paper aims to answer the question: which factors play a role in a successful implementation of self-management health innovations? Methods We conducted a narrative review of academic literature to explore factors related to successful implementation of selfmanagement health innovations. We f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 31 publications
(45 reference statements)
0
6
0
Order By: Relevance
“…The findings of our review, focused on mental health, are similar to systematic reviews examining implementation of self-management interventions in other settings, including physical health care settings. van Beest and colleagues [ 17 ] identified facilitating factors which included a tailored intervention that could adapt to organisational changes, and the involvement of multi-disciplinary teams. Whilst involvement of multi-disciplinary teams was not found to be a facilitator in our review, we did find that the lack of involvement from multiple disciplines was a barrier [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The findings of our review, focused on mental health, are similar to systematic reviews examining implementation of self-management interventions in other settings, including physical health care settings. van Beest and colleagues [ 17 ] identified facilitating factors which included a tailored intervention that could adapt to organisational changes, and the involvement of multi-disciplinary teams. Whilst involvement of multi-disciplinary teams was not found to be a facilitator in our review, we did find that the lack of involvement from multiple disciplines was a barrier [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…A recent narrative review [ 17 ] of self-management health interventions across multiple chronic conditions found that factors which can facilitate successful implementation included involving service users, engaging with local and business partners, involving stakeholders within the external system, tailoring the intervention, using multi-disciplinary teams, gathering feedback on effectiveness, having a feasible business model, adapting to organisational changes and anticipating changes that will be required within the healthcare system. An earlier synthesis [ 18 ] of factors influencing the adoption of self-management interventions for long-term illnesses identified factors related to patients, healthcare professionals and managers.…”
Section: Introductionmentioning
confidence: 99%
“…They can be considered as a means of punishment rather than giving them power. Therefore, innovation should not only measure results, but also support self-management processes [13][14][15] . The patients' awareness of asthma management techniques was found to be at medium level, showing that there is a need to improve patients' level of awareness about the use of asthma medications and devices in general in order to achieve a higher degree of awareness in the future.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies about the implementation of self-management health innovations have led to the identification of success factors for innovation, such as the 'involvement of end-users, partners, or stakeholders' (Van Beest et al 2020). The evaluation of self-management health innovations should be extended and tailored to those originating from PBR.…”
Section: Successful Implementation Of Self-management Health Innovationsmentioning
confidence: 99%